Measuring Emotion Understanding with the Rasch Model - Delgado, Ana R. (2016)
The aim of this study was to construct emotion understanding items from the Rasch Model approach by experimenting through comparison between verbal /image response format. The participants were 204 subjects from a Spanish community sample. A randomized experiment was carried out to test the effect of response format (verbal/image) and participants’ gender on the emotion understanding Rasch measurements. The effect on item difficulty of the social distance (close/far) was also contrasted. No interaction effect was found. Response format had a significant effect on measurement regardless of gender: the verbal response format was easier than the image one. There were significant gender differences on emotion understanding favoring women. Items describing situations with close receivers were significantly easier than the items showing far recipients.